Faktor-Faktor yang Mempengaruhi Kinerja Pegawai PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk - Farah Noor Ayuningtyas (Jurnal Bingkai Ekonomi (JBE), 2019)
The purpose of this study is to determine the effect of job satisfaction, work environmenton, and motivation of employee performance PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk. Data were obtained through questionnaires and interviews. The sample used in the study of 108 respondents. Results are expected to provide useful information to both leaders and employees. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis using multiple regression analysis to determine the effect of independent variables on the dependent variable, but before the test is done first tested the validity and reliability testing as well as testing requirements. The analysis shows that there is there is the influence of experience on the performance, and influence work environment on the performance, the influence of motivation positively and significantly of the performance of Employee PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk.